(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
What insights can informational analysis provide regarding the ramifications predicted by constructal design? The first step in answering this research question is to consider symmetric and asymmetric flow architectures. In the symmetric case, radial multi-branching shows diminishing returns of diversity (measured by the system’s informature) in line with high thermofluid performance. In asymmetric flow architectures, assuming an evolution toward maximum complexity (as defined in information theory), patterns emerge like sap distribution in leaves.